Return on Investment (ROI) training evaluation in Malaysian SMEs : factors influencing the adoption process - Luqman Hakim, Satiman; Nur Naha, Abu Mansor; Nadiatulhuda, Zulkifli (Emerald Publishing Limited, 2015)
Abstract